Distribution characteristics of aerosol microorganisms in bronchoscopy room and the risk assessment of nosocomial infection - Zhu, Wen; Xu, Yuehua; Chen, Ting; Shi, Minhua (Frontiers in Public Health, 2025)
ObjectiveA large number of aerosols containing pathogenic microorganisms can be produced during bronchoscopy. The aim of the study is to evaluate the risk of nosocomial infection by pathogenic microorganisms after bronchoscopy. The distribution characteristics of aerosol microorganisms were detected before and after bronchoscopy, and then compared with the distribution characteristics of the patients’ respiratory pathogens.MethodsA total of 152 patients underwent bronchoscopy in the bronchoscopy room from May 06, 2024 to June 30, 2024. Airborne microorganisms were collected in the bronchoscopy room before and after the bronchoscopy, then cultured, counted and identified, to analyze the species, numbers and changes of microorganisms. At the same time, the data of respiratory pathogens and nosocomial infection of all patients were collected to evaluate the correlation between air microorganisms and respiratory pathogens, and the risk of nosocomial infection.Results(1) The concentration of air microorganisms after bronchoscopy was 89.60 ± 63.52 CFU/m3, significantly higher than 43.80 ± 26.70 CFU/m3 before bronchoscopy (p < 0.001). The increase in air microorganism concentration was in accordance with the total number of patients and the number of patients with respiratory infectious diseases on the same day (p < 0.001). After bronchoscopy for patients with infectious diseases, the concentration was significantly higher than that for patients with non-infectious diseases (p < 0.05). (2) The bacteria accounted for 75.34, 70.35% of the total aerosol microorganisms, fungi 22.17, 26.80% before and after bronchoscopy. The bacteria mainly included Micrococcus luteus, Staphylococcus epidermidis, Staphylococcus hominis, Haemophilus influenzae, Neisseria faunalis, Staphylococcus capitis, etc. The fungi mainly included Aspergillus flavus, Aspergillus niger, Saccharomyces albicans, Penicillium spp., etc. (3) The increase in air microorganisms after bronchoscopy was consistent with the distribution of pathogens causing respiratory infections in patients (p < 0.001). The increased pathogens were mainly composed of common respiratory pathogens, but it did not increase the risk of nosocomial respiratory infections in patients (p = 0.735).ConclusionBronchoscopy can increase the concentration of aerosol microorganisms. The increased microorganisms are related to the respiratory pathogens of patients, which are mainly the common pathogens of pulmonary infection. This, however, does not increase the risk of nosocomial respiratory infection.